HUBUNGAN GAYA BELAJAR DENGAN HASIL BELAJAR SISWA PADA MATERI KESETIMBANGAN KIMIA - Syarifah Rauf Laudzaunna; Lisa Utami (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2021)
Abstract This research aimed at knowing whether there was a correlation between students’ learning style and their learning achievement. It was a correlational research. Collecting the data was done through learning style questionnaire, cognitive learning achievement test, and documentation. The subjects of this research were the students at Senior High School of Tri Bhakti Pekanbaru, and the object was the correlation between students’ learning style and their learning achievement on Chemical Equilibrium lesson. The samples were the eleventh-grade students of Natural Science that were 40 students. Total sampling technique was used in this research. The data were processed and analyzed by using Pearson product moment correlational test formula. Based on the research findings and data analyses, Sig. (2-tailed) score between students’ learning style and their learning achievement was 0.001 and it was lower than 0.05 (0.001<0.05), it meant that there was a positive correlation between students’ learning style and their learning achievement. The score of robserved of the correlation between students’ learning style and their learning achievement was 0.498 and it was higher than rtable 0.312 at 5% significant level (0.498>0.312), so it could be concluded that Ha was accepted and H0 was rejected (there was a correlation between students’ learning style and their learning achievement). The majority of the students had visual learning style type with 58% percentage, the percentage of students having auditory learning style was 27%, and the percentage of students having kinesthetic learning style was 15%. If these results were interpreted to the guideline table, the score 0.498 was between 0.40 and 0.70, and it meant that the correlation between students’ learning style and their learning achievement was medium or enough.